2018
DOI: 10.1186/s12890-018-0756-8
|View full text |Cite
|
Sign up to set email alerts
|

Guideline adherence in hospital recruited and population based COPD patients

Abstract: BackgroundEvidence from several studies show poor guideline adherence to COPD treatment, but no such study has been undertaken in Norway. The objectives of this study, was to estimate and compare the guideline adherence to COPD treatment in general population-based and hospital-recruited COPD patients, and find possible predictors of guideline adherence.MethodsFrom the prospective, observational EconCOPD-study, we analysed guideline adherence for 90 population-based COPD cases compared to 245 hospital-recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
6
1
Order By: Relevance
“…The study demonstrated that for 59.8% patients with confirmed COPD inhaled medications were prescribed in line with 2009 GOLD guidelines. The overall guideline adherence to COPD treatment for populationbased COPD cases has been reported significantly lower than amongst hospital-recruited COPD patients [30]. However, more patients appeared to be overtreated for their GOLD grade than in our study, 37.7% versus 8%, respectively (overprescribing of inhaled corticosteroids in COPD has been reported in a number of countries [13,28,[31][32][33].…”
Section: Discussioncontrasting
confidence: 58%
“…The study demonstrated that for 59.8% patients with confirmed COPD inhaled medications were prescribed in line with 2009 GOLD guidelines. The overall guideline adherence to COPD treatment for populationbased COPD cases has been reported significantly lower than amongst hospital-recruited COPD patients [30]. However, more patients appeared to be overtreated for their GOLD grade than in our study, 37.7% versus 8%, respectively (overprescribing of inhaled corticosteroids in COPD has been reported in a number of countries [13,28,[31][32][33].…”
Section: Discussioncontrasting
confidence: 58%
“…In controlled trials within this review, UC was described as: standard care for COPD, 18 the care usually received from their physicians, 44,46 or medical center, 19,41,48 according to relevant chronic disease clinical practice guidelines, 20,43,47 or was not described. 13,22,37 People with COPD receive less specialized medical care than people living with other chronic conditions 72 and health professional knowledge of, and adherence to clinical practice guidelines specific to COPD have been estimated to be as low 6.7% for communitybased people living with COPD 73 and range between 29.8% 73 and 36% for hospital-based registry data. 74,75 The difficulty with interpreting comparisons between CBT and usual care lies in the absence of information concerning what constituted usual care, especially where key components of usual care might improve psychological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important achievement, as influenza vaccination lowers the likelihood of respiratory infections and can reduce exacerbation rates [1,24,25]. Thus, the result obtained for Germany can be considered acceptable, especially when compared to other reported vaccination rates in patients with COPD, such as 49% in Swiss patients, or 34% in population-based and 71% in hospital-based patients in Norway [23,26].…”
Section: Discussionmentioning
confidence: 99%